Synthesis and Antimicrobial Study of Some New Chlorosubstituted Δ2-Pyrazolines - S. Deshmukh, Meghana; Rajput, P.R.; Chincholkar, M.M. (Asian Journal of Chemistry, 2010)
Chlorosubstituted 2´-hydroxy chalcones were allowed to react with phenylhydrazine hydrochloride in DMSO containing a little piperidine to give Δ2-pyrazolines in 2.5 h and yields were found to be 75-85%. Δ2-pyrazolines showed antibacterial activity to a considerable extent when assayed against some common human pathogens.